The Effect Of Interest Rate Perception And Credit Procedures On Car Purchase Decisions Mediated By Purchase Interntion In Pt. Maybank Indonesia Finance Medan Branch 2021 - Sormin, Maduma; Saparso, Saparso; Wahyoedi, Soegeng (Publisher Cv. Inara, 2022)
This study discusses the interest rate perceptionand credit procedures on car buying decisions mediated by purchase interest variables. The results of the research on the first hypothesis are the influence of perceptions of interest rates on purchase interest with a value of t-count 5.831> t-table 1.99 (p 0.000 <0.05). The second hypothesis in this study is that there is an effect of credit procedures on purchase interest (2.709> 1.99); (p 0.007 <0.05). The third hypothesis in this study is that there is an influence of interest on car buying decisions (2,687>1.99); (p 0.007 < 0.05). The fourth hypothesis in this study is that there is an effect of interest rate perceptionon car buying decisions (3,524>1,99); (p 0.000 < 0.05). The fifth hypothesis in this study is that there is an effect of credit procedures on car buying decisions (2,475> 1.99); (p 0.001 < 0.05). The sixth hypothesis is that the purchase interest variable cannot mediate the relationship between perceptions of interest rates on purchasing decisions (2.392 > 1.99). The seventh hypothesis is that the purchase intention variable cannot mediate the relationship between credit procedures and purchasing decisions (t 1.852 < 1.99).